Endovascular technique simulator for Neuroradiology learning - SOUZA, João Renato Figueiredo; BARROS, Edgar Marçal de, FILHO; JUCÁ, Carlos Eduardo Barros; ROLIM, Juliana Paiva Marques Lima (Arquivos de Neuro-Psiquiatria, 2020)
Background: Vascular cerebral infarction (or stroke) is recognized as the third leading cause of death worldwide, and acute arterial occlusion comprises the main mechanism underlying ischemic stroke. Cerebrovascular diseases are treated by intracranial endovascular interventions employing minimally invasive intravascular techniques, such as neuroimaging. Conducting practical training in this area is a necessary task since patient safety is a considerably significant factor. There has been a steady increase in scientific research focused on validating endovascular simulation as a tool for training interventionists in endovascular procedures. Current literature confirms the idea that there is a beneficial role of simulation in endovascular training and skill acquisition and technique improvement. Objective: To develop an endovascular technique simulator for learning Neuroradiology. Methods: The methodology consisted of developing a simulator using 3D printing technology. Results: A literature search was carried out, commencing in August 2017, through consultation of the Medical Literature Analysis and Retrieval System Online (MEDLINE) and Latin American and Caribbean Health Sciences Literature (LILACS) databases, using the PubMed and BIREME websites, respectively. Meetings were held between the neuroradiologist specialist and programmers to develop the simulator, which was carried out in three phases: design of the arterial system, design of the prototype of the arterial system in computer graphics, and confection of the arterial system simulator in 3D. Conclusion: The simulator is ready for testing by residents and can enable the student to learn through simulations that reproduce, as realistically as possible, the situation to be subsequently experienced using a concrete tool.
Keywords: Endovascular Procedures; Education